Pirate latitudes : a novel - Crichton, Michael, 1942-2008 (HarperCollins, 2009)
The Caribbean, 1665. Pirate captain Charles Hunter, with backing from a powerful ally, assembles a crew of ruffians to take the Spanish galleon, "El Trinidad," guarded by the bloodthirsty Cazalla, a favorite commander of the Spanish king himself.